2023
DOI: 10.1001/jamapsychiatry.2022.4599
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Abnormalities in Different Clinical Stages of Psychosis

Abstract: ImportanceAbnormal sleep is frequent in psychosis; however, sleep abnormalities in different stages (ie, clinical high risk for psychosis [CHR-P], early psychosis [EP], and chronic psychosis [CP]) have not been characterized.ObjectiveTo identify sleep abnormalities across psychosis stages.Data SourcesWeb of Science and PubMed were searched between inception and June 15, 2022. Studies written in English were included.Study SelectionSleep disturbance prevalence studies and case-control studies reporting sleep qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…In this advanced phase of the disease, normally, many drugs affecting cognition, depression, anxiety, behavior symptoms, and mobility are prescribed with a tailored therapy that could be specific for each patient. This topic was recently emphasized in the context of psychosis, where authors underlined different sleep disorders throughout the course of the disease and different psychosis stages showed distinct abnormalities in sleep quality, architecture, and spindles [ 128 ]. These findings altogether suggest that sleep disorders could become a core treatment in different neurodegenerative diseases, such as psychosis, Parkinson’s disease, and dementia [ 129 , 130 ].…”
Section: Right Medication At Right Disease Statementioning
confidence: 99%
“…In this advanced phase of the disease, normally, many drugs affecting cognition, depression, anxiety, behavior symptoms, and mobility are prescribed with a tailored therapy that could be specific for each patient. This topic was recently emphasized in the context of psychosis, where authors underlined different sleep disorders throughout the course of the disease and different psychosis stages showed distinct abnormalities in sleep quality, architecture, and spindles [ 128 ]. These findings altogether suggest that sleep disorders could become a core treatment in different neurodegenerative diseases, such as psychosis, Parkinson’s disease, and dementia [ 129 , 130 ].…”
Section: Right Medication At Right Disease Statementioning
confidence: 99%
“…the Pittsburgh Sleep Quality Index, PSQI) enable the evaluation of the prevalence of sleep complaints in SSD as well as to quantify subjective sleep quality in patients with SSD compared with non-clinical populations. Of note, while sleep disturbance prevalence is 20-25% in the general population, several studies showed higher prevalence (≥50%) in patients with SSD, as recently reported by a meta-analysis (Bagautdinova et al, 2023). Besides subjective sleep assessments that are inexpensive and easy to implement in large clinical cohorts, several objective measures collected with actigraphy, electroencephalography, and polysomnography allow for the quantification of altered sleep characteristics in patients with SSD compared to healthy controls.…”
mentioning
confidence: 92%
“…Cognitive dysfunction is a core feature of SSD and represents one of the best predictors of poor functional outcomes in patients with SSD. In recent work, we reported that decreased prefrontal spindle density was associated with worse working memory performance in patients with schizophrenia relative to the control group (Buchmann et al ., 2014). Furthermore, several sleep studies have shown that, in chronic patients with schizophrenia, reduced spindle density was associated with impaired memory consolidation, involving both procedural and declarative memory (Manoach and Stickgold, 2019).…”
mentioning
confidence: 96%
“…In a recent meta‐analysis, our research group established that sleep disturbance prevalence was 50% across stages of psychosis, compared with less than 25% in the general population, thus representing a relevant but currently undertreated clinical target in patients with SCZ (Mayeli et al, 2023). In that meta‐analysis, sleep spindles, a sleep‐specific oscillatory activity occurring during NREM, were found to be defective across stages of psychosis, thus suggesting that a reduction in sleep spindles is present and persists throughout the course of the disorder (Bagautdinova et al, 2023). Furthermore, altered spindle parameters in SCZ have been associated with a range of clinical outcomes, including increased severity of positive and negative symptoms, cognitive impairment and poorer functional outcomes (Ferrarelli, 2021).…”
Section: Introductionmentioning
confidence: 99%